BERBAGAI PENDEKATAN DALAM STUDI ISLAM: NORMATIF, INTEGRATIF, DAN INTERDISIPLINER - Dhini Ayu Triningsih; Yusnita Yusnita (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
An approach is a perspective or paradigm found in a field of science which is then used in understanding religion. In this case it is the Islamic religion. Islam can be seen in several aspects that are in accordance with its paradigm. In the Islamic religion, the Islamic study approach is divided into 3 types of approaches, 1) Normative Approach, 2) Integrative Approach, and 3) Interdisciplinary Approach. The approach method used in studying this topic is literature study in which the literature taken is adjusted to the subject of discussion and analyzed. in depth so that conclusions, findings can be drawn, and can be studied as a source of information in the future